Strategic ejaculate adjustments and mismatches: are males paying sperm senescence costs?. Issue 4 (3rd July 2020) - Magris, Martina; Chimetto, Gianluca; Pilastro, Andrea
Abstract : In many species, males show anticipatory plasticity for sperm production, which they adjust to match perceived mating opportunities. While the strategic adjustment of sperm production is likely to be beneficial, it may be also associated with costs, including those arising from the expression of a phenotype that is poorly matched to the conditions that males will subsequently experience. Mismatch costs are exacerbated by trade-offs between investment in the ejaculate and investment in other traits and by trade-offs among individual ejaculate traits. Trade-offs, in fact, may determine a decrease in male competitiveness, due to impaired ability to obtain copulations or to reduced ejaculate quality. We explored mismatch costs using male guppies, which are known to increase sperm production, but reduce their investment in sexual behaviour, when maintained in the presence of females. Increasing ejaculate size in the absence of females could impose costs that would be paid when an opportunity to mate eventually arises. One of such costs may involve male post-copulatory competitiveness and may be associated with increased sperm senescence. To explore mismatch costs, firstly we induced two groups of males to differentiate their sperm production by exposing them or not to female stimuli. Then, we isolated them to prevent matings and have their sperm ageing. Finally, we compared ejaculate quality between the groups. Contrary to expectations, we found that female-stimulated males did not suffer from increased sperm senescence. These costs are probably minimized by the high level of plasticity associated with this trait, resulting in sperm production being quickly re-adjusted to a new environment. Other types of mismatch costs may be more relevant, for example, those related to trade-offs with sexual behaviour.